INTERRITUALITY SEBAGAI MEDIUM KOMUNIKASI LINTAS AGAMA: BELAJAR DARI SEMBAHYANG KING HOO PING UMAT KHONGHUCU DI SEMARANG - Adrianus Bintang Hanto Nugroho,SIP.,MA. (Universitas Katolik Soegijapranata, 2023)
For more than thirty years, the existence of the religion of Khonghucu was not recognized by the New Order government. During Abdurrahman Wahid's presidency, the government issued a regulation recognizing the religion. Soon afterward, the Khonghucu community actively engaged in various interreligious communication practices to maintain interreligious harmony. Interestingly, Khonghucu community in Semarang established practice of interreligious communication through the King Hoo Ping prayer ritual. In that annual prayer, religious leaders are invited to actively participate in the private ritual of the Khonghucu community. This kind of interrituality practice can be a medium for interreligious encounter and communication. Using Marianne Moyaert's concept of interrituality, this paper aims to describe the interritual practice of King Hoo Ping interreligious prayer. This paper wants to examine how the host's religious hospitality can turn strangers and outsiders into being guests in the host's ‘religious house’.